2007
DOI: 10.1523/jneurosci.4284-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Temperature on Neural Activity in the Hippocampus: Regulation of Resting Membrane Potentials by Transient Receptor Potential Vanilloid 4

Abstract: Physiological body temperature is an important determinant for neural functions, and it is well established that changes in temperature have dynamic influences on hippocampal neural activities. However, the detailed molecular mechanisms have never been clarified. Here, we show that hippocampal neurons express functional transient receptor potential vanilloid 4 (TRPV4), one of the thermosensitive TRP (transient receptor potential) channels, and that TRPV4 is constitutively active at physiological temperature. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
195
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(214 citation statements)
references
References 45 publications
14
195
0
2
Order By: Relevance
“…Indeed, it has been previously reported [10] that 4α-PDD (a TRPV4 agonist) activates currents in hippocampal neurons in primary cultures. Therefore, we compared the effects of this agonist between primary hippocampal cultures and slices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been previously reported [10] that 4α-PDD (a TRPV4 agonist) activates currents in hippocampal neurons in primary cultures. Therefore, we compared the effects of this agonist between primary hippocampal cultures and slices.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, presence of temperature sensitive ion channels in the neurons may mediate the effects of cooling. In hippocampal cultures, the presence of transient receptor potential channel V (TRPV)-4 that is activated at temperatures within the physiological range (>27°-34°C) has been reported [10].…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of two anti-TRPV4 antibodies is described elsewhere (32,33). ␤-Catenin and mouse TRPV4 cDNA were generously provided by Dr. M. Takeichi and Dr. M. Caterina, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This endocannabinoid-induced plasticity could also be triggered by other TRP channels. Indeed Wanabe et al (2003) showed that anandamine could activate TRPV4 via epoxyeicosatrienoic acid and TRPV4 is known to be expressed in hippocampus (Shibasaki et al, 2007). Another possibility is that TRPV1 triggers LTD via a nonconducting function (Kaczmarek, 2006) or via a capsaicin-resistant TRPV1.…”
Section: Review Of Cavanaugh Et Almentioning
confidence: 99%